Histopathological data of iron and calcium in the mouse lung after asbestos exposure. - Trevisan, Elisa; Zabucchi, Giuliano; Pascolo, Lorella; Pascotto, Ernesto; Casarsa, Claudia; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; Zweyer, Marina; Borelli, Violetta (Data Brief, 2016)
This data article contains data related to the research article entitled, "Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice" [1]. Asbestos fibers disrupt iron homeostasis in the human and mouse lung, leading to the deposition of iron (Fe) onto longer asbestos fibers which forms asbestos bodies (AB) [2]. Similar to Fe, calcium (Ca) is also deposited in the coats of the AB. This article presents data on iron and calcium in the mouse lung after asbestos exposure detected by histochemical evaluation.